OPTIMALISASI MESIN BENDING AKRILIK DENGAN METODELOGI TAGUCHI - Danar Jaya, Rangga; Karmin, Karmin; Mardiana, Mardiana (MACHINERY Jurnal Teknologi Terapan, 2025)
The acrylic bending machine used in this study is a development of a machine that has been circulating in the market and also a development of the previous acrylic bending machine which aims to optimize the acrylic bending tool in order to produce an acrylic bending machine that is more precise in temperature regulation and bending results, this test is carried out by means of experimental data collection or direct testing and data analysis methods used is a Taguchi method with an orthogonic array L16 which is assisted by Minitab software and the results are obtained that the temperature, time and angle settings are quite influential on the bending results in each thickness, and the variation of each combination is not too significant and it can be concluded that the acrylic bending machine in this study can work more optimally because of the stable temperature setting and also good bending results, especially in acrylic 1.5 mm to 3 mm and also this machine can also bend 5 mm thick acrylic but requires a longer heating time